(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Secret writing is the art of covered or hidden writing. The art of secret writing is meant to create a message unreadable by a third party however doesn’t hide the existence of the secret communication. This paper is meant as a technical introduction to secret writing for those unacquainted with the field. Invisible inks are generally used for secret writing. These are fluids used to write hidden messages that do not appear unless exposed by a revealing process. Invisible inks can be classified into three main categories: those that are revealed by heat, those revealed by chemical reactions and those that are visible under ultraviolet light. Some common household invisible inks are diluted fruit juices, vinegar and laundry detergent, all which can be applied by a paintbrush, special invisible ink pen or even a toothpick, Historically, used in times of war by governments and insurgents alike. The chemical processes of invisible inks are well known, so a variety of detection methods exist. The simplest invisible ink experiment consists of dipping a brush in vegetable juice, biological fluids and different chemicals and writing on a piece of blank varieties of paper. When the “ink” dries, it will be invisible to the naked eye, but if the paper is held up to a moderate heat source such as a light bulb, a radiator or an iron using UV lamp to deciphering invisible writing. Many other mild chemicals also used for restoration of secret writing.